Comparison of the physical activity in the daily program between youth basketball players and adolescents aged from 16 to 17 years in the Czech Republic - Reich, Petr; Rechtik, Zdeněk; Miklánková, Ludmila; Prukner, Vítězslav (Journal of Education, Health and Sport, 2016)
Life-style is an important part of human health. It is an essential part of physical, psychological and social health. In this part of the research are presented the results obtained in the Czech Republic: the volume and intensity of physical aktivity. Purpose: The aim of the research is comparison of the physical activity in the daily program between youth basketball players and regular adolescents in the Czech republic. The project " Health, Fitness and education in Visegrad Countries and neighboring Countries " is focused on mapping and comparison of selected aspects of lifestyle and somatic characteristics of adolescents from Visegrad and other European countries (Poland, Czech Republic, Hungary, Slovakia and Ukraine). Methods: The Czech Republic participated in the project with 227 probands (144 boys, 83 girls), basketball players were 137 (93 boys, 44 girls) and 90 pupils from high-schools in the Czech Republic (51 boys, 39 girls). There was „Mezinárodní dotazník pohybové aktivity“ (IPAQ – International Physical Activity Questionnaire, short version) used to collect datas about physical activities. Results: There were not found significant differences between sexes in the number of days spent with physical activities. There were also not found significant differences between sexes in the level of physical activity per day. Conclusion: The results of the project will help not only to compare data on physical activity of adolescents in individual countries, but also to examine it in the context of the effectiveness of preventive measures in the participating countries.